The Road to Digital Single Market: How the EU Can “Enter That Orbit”? - Bonis, Konstantinos Taxiarchis P. (HAPSc Policy Briefs Series, 2023)
Covid-19 pandemic was the breaking-even point for many of the EU’s orientations. One of them, was the digital agenda of the Union. Deeply inside the mind of the EU’s stakeholders, the transformation of single market, into a digitalized one, was the first step. Despite the ambitious perspective of that incentive, the truth lies elsewhere; In order to digitalize the traditionally lucrative single market, huge effort is required, adequate capitals and on the top of all, the member-states socio-political consent. It is neither an easy nor an ultra-difficult step for the European Union. The proper synergies of supranational and national level will maximize EU’s efficiency and optimality. In that paper, the evolution of Digital Single Market and the right path to achieve that target is being analyzed as thoroughly as possible.